Kemitraan United State Agency for International Development dan Persatuan Waria Kota Surabaya dalam Penanggulangan HIV-AIDS (2014-2016) - Pangribuan, Purnama; Purbantina, Adiasri Putri (Global and Policy Journal of International Relations, 2022)
This study aims to understand the social interactions and health services of transwomen HIV/AIDS survivors in Surabaya which are associated with the role of the United State Agency for International Development (USAID) in the Global Health Initiative discourse. This study uses a qualitative approach using interview guidelines and case study methods specifically to answer the research objectives. The information collected is information about the role of the Surabaya City Waria Association (Perwakos) in tackling HIV/AIDS in relations with USAID partners as International Donor Institutions, Program Implementation, Policy Development, Advocacy Assistance and Provision of Health Services. Taking into account the conditions, data was taken from five transwomen who were selected as informants who joined Perwakos using purposive and snowball sampling. This study used a qualitative analysis method through literature analysis and in-depth interviews with several representatives from the Surabaya City Waria Association (Perwakos).DOI: https://doi.org/10.33005/jgp.v10i01.3568